“Well-foundedness” and investigation (Academic Journal of Internal Affairs, 2012)
Providing a thorough analysis of Hungarian criminal procedure law, the author investigates the precise meaning and content of the requirement for the suspicion to be “well-founded”.
Keywords: suspicion; investigation; forensics